The Effect of Junior High School Vocabulary Mastery Using Word Wall Web - Rika Amelia; Selviyanti Nur Zubaedah; Khansa Edlyka; Salwa Azilah; Siti Nurul Azkiyah (Universitas Pahlawan Tuanku Tambusai, 2023)
Educators and academics are increasingly interested in using digital tools and applications to enhance online education. The recent growth of online education has attracted this interest. An English teacher will be observed in a junior high school to assess students' vocabulary. The observation results showed that students had difficulty in responding to English. The researcher implemented the Word Wall web as a vocabulary learning tool with the authorization of the teacher. Treatment sessions, pre-tests, post-tests, and surveys will assess students' progress and perception of Word Wall. Data analysis will determine students' word comprehension improvement. This study examines how online learning is based on word wall applications improves junior high school vocabulary. This study used Classroom Action Research. Pretest and posttest are objective tests used in this study. Somebody can use Word Wall in various subjects, not only language. With extra practice on Word Wall, students can increase their daily vocabulary. Researchers should explore different focus areas of English skills for similar research.